Children's thoughts on the social exclusion of peers with intellectual or learning disabilities. (28th January 2013) - Nowicki, E. A.; Brown, J.; Stepien, M.
Abstract Background Previous research has shown that children with intellectual or learning disabilities are at risk for social exclusion by their peers but little is known of children's views on this topic. In this study, we used concept mapping to investigate elementary school children's thoughts on why they believe their peers with intellectual or learning disabilities are sometimes socially excluded at school. Method Participants were 49 grade five and six children who attended inclusive classrooms. Interviews were digitally recorded and transcribed. We extracted 49 unique statements from the transcribed data, and then invited participants to sort the statements into meaningful categories. Results Sorted data were entered into matrices, which were summed and analysed with multi‐dimensional scaling and cluster analysis. A four‐cluster solution provided the best conceptual fit for the data. Clusters reflected themes on (1) the thoughts and actions of other children; (2) differences in learning ability and resource allocation; (3) affect, physical characteristics and schooling; and (4) negative thoughts and behaviours. Conclusions The overarching reason for social exclusion focused on differences between children with and without disabilities. This study also provided evidence that children are effective, reliable and competent participants in concept mapping. Educational and research implications are discussed.